Review of the genus Cerconychia Klapálek, 1913 (Plecoptera: Styloperlidae), with description of C. multiseta sp. nov. - Mo, Raorao; Liu, Hao; Kong, Fanbin; Li, Weihai (Zootaxa, 2021)
Species of the genus Cerconychia (Plecoptera: Pteronarcyoidea: Styloperlidae) are reviewed. A new species, C. multiseta sp. nov. is described from Cenwanglaoshan Mountain of western Guangxi Zhuang Autonomous Region, China. The new species is compared with related congeners. Complementary description or brief taxonomic comments are presented for C. brunnea Klapálek, 1913, C. flectospina Wu, 1962, C. livida Klapálek, 1913, C. sinensis Yang & Yang, 1995 and C. trilobata Mo, Yao, Wang & Li, 2019.